Design and scale‐up of an alkylated Minisci reaction to produce ethionamide with 4‐cyanopyridine as raw materials. (7th September 2017) - Liang, Zhongrui; He, Lichao; Wang, Wenchao; Zhou, Zhiyong; Ren, Zhongqi
Abstract: Tuberculosis is a serious bacterial infection in developing countries, especially in areas with drug resistance. The development of the anti‐tuberculosis drug ethionamide (ETA) is therefore particularly important. We have designed a new route for ETA synthesis and considered the drug's amenability to large‐scale manufacture. We evaluated different routes for the synthesis of ETA and selected the most suitable process for the industrial production of this material, which involved the Minisci reaction of 4‐cyanopyridine with propionic acid using a AgNO3 /(NH4 )2 S2 O8 catalyst system under acidic conditions. The effects of different parameters on the reaction were studied, and the production of the intermediate of 2‐ethyl‐4‐cyanopyridine was twice recrystallized from methanol to obtain pure ETA. In the Minisci reaction, the system was stirred for an additional 20 min at 80 °C after the addition of ammonium persulphate solution. The subsequent formation of thioamide was conducted at 40 °C to 60 °C for 1.5 h with a 1:5:2 molar ratio of 4‐cyanopyridine, propionic acid, and ammonium sulphide. The purity of the crude ETA reached 98.77  % after two recrystallization steps. This process could be scaled up on a much larger scale (1 kg), leading to the yield of alkylation reaction and overall yield of the production process as 44.06 % and 31.26 %, respectively. Abstract : A new route for industrial production of ETA was proposed by Minisci reaction of 4‐cyanopyridine with propionic acid using a AgNO3 (NH4 )2 S2 O8 catalyst system under acidic conditions and the purity of the ETA reached 98.77 % after two recrystallization steps. The alkylation and overall yields of the scaling up process were 44.06 % and 31.26 %, respectively.